2014
DOI: 10.3389/fpls.2014.00288
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of nitrogen isotope biogeochemistry in plant-soil systems: implications for the study of ancient agricultural and animal management practices

Abstract: Nitrogen isotopic studies have the potential to shed light on the structure of ancient ecosystems, agropastoral regimes, and human-environment interactions. Until relatively recently, however, little attention was paid to the complexities of nitrogen transformations in ancient plant-soil systems and their potential impact on plant and animal tissue nitrogen isotopic compositions. This paper discusses the importance of understanding nitrogen dynamics in ancient contexts, and highlights several key areas of arch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
265
2
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 313 publications
(279 citation statements)
references
References 194 publications
(295 reference statements)
7
265
2
5
Order By: Relevance
“…As illustrated in Table 2, the subsoil (i.e., 60-90 cm depth) had signifi cantly higher δ N at the topsoil in this study indicated that N was a product of m ultiple variables such as N fi xation, precipitation, rainstorm, and the use of chemical fertilizers. Several investigators had also demonstrated similar results, e.g., [66][67][68]. The authors mentioned above attributed this to atmospheric N 2 , which is usually the raw material for fertilizer production, and δ…”
supporting
confidence: 51%
See 1 more Smart Citation
“…As illustrated in Table 2, the subsoil (i.e., 60-90 cm depth) had signifi cantly higher δ N at the topsoil in this study indicated that N was a product of m ultiple variables such as N fi xation, precipitation, rainstorm, and the use of chemical fertilizers. Several investigators had also demonstrated similar results, e.g., [66][67][68]. The authors mentioned above attributed this to atmospheric N 2 , which is usually the raw material for fertilizer production, and δ…”
supporting
confidence: 51%
“…In contrast, when the soil depth profi le was increased, the value of δ 15 N became signifi cantly higher. According to [56,66,[74][75] It is noteworthy that this increase in δ…”
mentioning
confidence: 99%
“…Otherwise,δ 15 N values are able to provide information about the trophic level that an specific organism holds in the food chain Minagawa and Wada 1986). They are considered to increase generally between 3 and 5‰ with each trophic level up inside the food web Schwarcz and Schoeniger 1991), although some researchers suggest this range could be wider (Hedges and Reynard 2007;Szpak 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This δ 13 C variability is not only recorded in plants, as it is introduced also in higher trophic levels through their consumption, and plays an important role in the study of shepherding and livestock management (Tornero et al 2016a). Plants also take organic nitrogen from the soil, resulting in their δ 15 N values showing variations depending on natural or anthropic factors which affect the soil-plant system (Szpak 2014). Among the natural factors, the presence of organic material in the soil, temperature and water availability could be the most significant ones (Ambrose 1991;Handley et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although first seen as a source of error in paleodietary research, fertilization systematics are now being used to reconstruct the rise of intensive agriculture and its link to animal domestication, husbandry practices (e.g., complete captivity, controlled herds, and pasturing locales), and land use patterns (Balasse 2014, Hamilton & Thomas 2012, Makarewicz & Tuross 2012, Szpak 2014b). …”
Section: $B$ Isotopes and Paleoenvironmentsmentioning
confidence: 99%